PENGARUH BERKAS REKAM MEDIS TIDAK ADA DIRAK PENYIMPANAN BESERTA FAKTOR PENYEBABNYA TERHADAP LAMANYA WAKTU TUNGGU PASIEN BERULANG DI RS USU - MANURUNG, PIRMA IVAN RICKY (LP2MTBM MAKARIOZ, 2021)
Not finding medical record files when they are needed for service is a problem in the storage department. The failure to find medical record files is not only influenced by the storage system, but also by other departments. This is because medical record files that have been used for patient care will undergo processing first before they are returned to storage (filing). This study aims to determine the absence of BRM on the Diling shelf and what are the factors in the length of waiting time for repeat patients at USU Hospital. Research subjects are informants. This means that people in the research setting are used to provide information about the situation and conditions of the research setting. The main data source in qualitative research. Based on the results of observations of the activities of filing officers, they have not implemented tracers in the process of storing medical record files. The results of observations from 27 August 2018 to 29 August 2018 saw an average of 174 outpatient medical record file requests. In requesting medical record files, the filing officer was quite good at compiling the existing BRM. Of the 174 medical record files requested, an average of 7 medical record files or 4.0% of medical record files were not found in one day. Based on the results of observations in the filing section. Based on the results of the research above, no factors were found in the storage shelves that cause medical record files, ranging from the highest active files to the wrong file arrangement and the doctor's integrity being the lowest.